دراسة تأثير الحريق في التنوع الحيوي النباتي في بعض المواقع الحراجية في محافظة اللاذقية (سورية) - دركلت, أحمد; البساتنة, مروان; الشاطر, زهير (Latakia University Journal -Biological Sciences Series, 2019)
تمت دراسة التنوع النباتي في ثلاثة مواقع حراجية في محافظة اللاذقية هي (البسيط, كسب, ربيعة) والتي تعرضت لحرائق خلال السنوات الأربع الماضية (ت2 2004 في البسيط, تموز 2007 في كسب و أيلول 2007 في ربيعة). أظهر تحليل المعطيات بطريقة PCA و CA تأثير السفح بشكل واضح في حدوث الحريق. من ناحية أخرى, أظهرت النتائج تأثيراً واضحاً للحريق في التنوع النباتي ولكن هذا التأثير اختلف باختلاف المواقع وكان أكثر وضوحاً في موقع ربيعة. لم يظهر استخدام دلائل التنوع الحيوي المختلفة فروقاً واضحة بين المواقع. Plant species diversity has been studied on three sites in the Governorate of Lattakia (Bassist, Kassab, and Rabeea). The three sites faced fires during the last four years (November 2004 in Bassite, July 2007 in Kassab, and September 2007 in Rabeea). Using the methods of PCA and CA, data analysis showed a significant effect of exposure to triggering fire. On the other hand, the results showed a significant effect of fire on plant diversity, but this effect varied according to the site, and that was more significant on the site of Rabeea. The use of various indices of diversity didn’t show clear differences between the studied sites.